Southern African Lesbian and Bisexual Women Responses to Symptoms of Sexually Transmitted Infections. - Wikramanayake, Radhika M.; Paschen-Wolff, Margaret M.; Matebeni, Zethu; Reddy, Vasu; Southey-Swartz, Ian; Sandfort, Theo G. M. (Archives of Sexual Behavior, 2020)
Sexually transmitted infection (STI) in lesbian and bisexual women is a relatively unexplored topic, particularly for women from low- and middle-income countries. Despite perceptions that women who have sex with women (WSW) are at negligible risk of contracting STI, existing research demonstrates that WSW do become infected with STI. Given the opposition between assumptions of invulnerability and the observed risks, we explored how WSW would respond to symptoms of STI (i.e., wait until symptoms passed, see a medical doctor, and inform sexual partners). We used data collected as part of a collaboration between academic researchers and community-based LGBTQ organizations in Botswana, Namibia, South Africa, and Zimbabwe. Chi-squared tests were used to test whether participants' responses to hypothetical STI symptoms varied in relation to several intrapersonal, interpersonal, and structural factors. Multivariable logistic regression (backward) was used to assess whether these variables were independently associated with women's responses. Most women would be proactive in response to potential STI symptoms and would see a medical doctor. However, most women would not inform their sexual partner of symptoms of STI. Findings demonstrate several intrapersonal, interpersonal, and structural factors that influence WSW's health agency, and show a clustering of high-risk factors among women who would not be proactive about their health. Our findings suggest the need for improved health and health care of WSW in Southern Africa.